CARBON SOURCES AND C:N RATIOS ON WATER QUALITY FOR NILE TILAPIA FARMING IN BIOFLOC SYSTEM - Silva, Ugo Lima (2017)
The use of biofloc technology (BFT) can improve fish production in regions with low water availability. Therefore, information on dynamics of water quality is essential for success in fish rearing. Thus, the objective of the present study was to evaluate the water quality for Nile tilapia farming in a system without water exchange, during the fingerling stage, using different sources of carbon and C:N ratios. A completely randomized experimental design was used in a 2x3 factorial arrangement, with two carbon (C) to nitrogen (N) ratios (10:1 and 20:1) and three carbon sources (sugar, molasses and cassava starch). The C:N ratio and carbon source affected the variables alkalinity, settleable solids (SS), turbidity and total suspended solids (TSS), showing significantly higher values at C:N ratio of 20:1 (P < 0.05). The best carbon source for microbial floc formation were the molasses and sugar, under C:N ratios of 10:1 and 20:1. The stability of the monitored water quality parameters occurred from 6 to 7 weeks of rearing. The growth performance of Nile tilapia in BFT system fertilized with different organic carbon sources was not significantly different (P < 0.05) between treatments. The use of molasses to fertilize BFT systems can reduce costs of production in regions where this product is available.